Efektivitas Johnson Fetal Roll Dalam Menentukan Tafsiran Berat Janin Pada Ibu Inpartu - Baiq Nurmala Wulandari; Dini Dwi Rahayu; Fitra Arsy Nur Cory'ah (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
Birth weight wass a significant indicator for birth. According to Taylor and Ward, fetal weight is the single most important factor in determining fetal safety. Fetal weight assessment technique wass done by abdominal palpation. The tool commonly used to measured the Fundal uterine of pregnant women to interpret fetal weight with the Johnson Toshach formula was the metline with a centimeter scale. Pusposeof the study was to create a simple tool that can facilitate health workers, especially midwives, in determining prediction of birth weight directly. This study used a study design. analytic observational cross-sectional design. The population of this study were pregnant women in the third trimester with signs of labor. The research sample was 65 people. Based on the table, the age of the most respondents wass 20-30 years with a percentage of (49.2%), the education of the most respondents is higher education/Equivalent with a percentage of 3,4%, the parity of the most respondents wass primipara with a percentage of 53,8%, the most pregnancy age respondents are pregnancy age 39-40 weeks with a percentage of 69,2%, the highest BBL was 2500-4000 grams with a percentage of (90,89). Conclusion of the study was JFR can be used to facilitate health workers (midwives) in providing care, especially determining prediction of birth weight.